2021
DOI: 10.3390/ijerph182212257
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction and Associated Health Outcomes in Adult Populations: A Systematic Review

Abstract: Background: Smartphones play a critical role in increasing human–machine interactions, with many advantages. However, the growing popularity of smartphone use has led to smartphone overuse and addiction. This review aims to systematically investigate the impact of smartphone addiction on health outcomes. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to carry out the systematic review. Five electronic databases including Medline, Web of Science, Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 64 publications
6
86
0
3
Order By: Relevance
“…The smartphone addiction could be represented as nomophobia [ 23 ], phubbing [ 24 , 25 ] or social media addiction [ 26 ]. A recent systematic review revealed that smartphone addiction could be detrimental to physical and mental health [ 27 ], interestingly, another review reported that social media addiction found a negative but small relationship between social media addiction measures and well-being [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The smartphone addiction could be represented as nomophobia [ 23 ], phubbing [ 24 , 25 ] or social media addiction [ 26 ]. A recent systematic review revealed that smartphone addiction could be detrimental to physical and mental health [ 27 ], interestingly, another review reported that social media addiction found a negative but small relationship between social media addiction measures and well-being [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smartphone addiction (SPA) may be common among young adults, in particular college students, in part because of interests to develop social relationships in virtual networks, the existence of several online platforms to make such relationships, and skills in using modern technologies via their phones [ 31 , 32 ]. SPA has been associated with poor well-being, especially psychological (e.g., poor sleep quality, feelings of loneliness, mental fatigue, role conflict, and depression) [ 31 , 33 ]. SPA may also lead to somatic problems such as headache, painful neck and wrist, and visual impairment [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a few other terms have been used to describe this phenomenon: problematic mobile phone use, mobile phone addiction, excessive mobile phone use, and compensatory mobile phone use ( 9 ). PMPU is characterized by excessive attention and uncontrolled dedication to one's cell phone use ( 10 ).…”
Section: Introductionmentioning
confidence: 99%